How Integrated Reporting Amplifies Capital Intensity to Drive Firm Value Growth? - Angelita, Rosalina; Saputra, Dian (E-Jurnal Akuntansi, 2025)
Firm value reflects performance and competitiveness, which are the main concerns for investors, especially in the consumer cyclicals sector which is sensitive to economic cycles. Inconsistencies in previous research regarding the effect of working capital management and capital intensity on firm value requires further study. This study uses panel data from 83 companies selected by purposive sampling during the 2021-2023 period. The analysis employs a moderation regression method using EViews software. The results show that capital intensity has a significant positive effect on firm value, while working capital management has no significant effect. Integrated reporting strengthens the relationship between capital intensity and firm value, but doesn’t moderate the relationship between working capital management and firm value. These findings highlight the importance of investment in fixed assets and reporting transparency to increase firm value. This study provides insights for managers on leveraging integrated reporting in creating sustainable firm value. Keywords: Working Capital Management; Capital Intensity; Firm Value; Integrated Reporting; Consumer cyclicals